Gold-catalyzed regiospecific annulation of unsymmetrically substituted 1,5-diynes for the precise synthesis of bispentalenes - Tavakkolifard, Sara; Sekine, Kohei; Museridze, Ketevan; Michel, Elena; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Chemistry - a European journal, 2019)
Precise control of the selectivity in organic synthesis is important to access the desired molecules. We demonstrate a regiospecific annulation of unsymmetrically substituted 1,2-di(arylethynyl)benzene derivatives for a geometry-controlled synthesis of linear bispentalenes, which is one of the promising structures for material science. A gold-catalyzed annulation of unsymmetrically substituted 1,2-di(arylethynyl)benzene could produce two isomeric pentalenes, but both electronic and steric effects on the aromatics at the terminal position of the alkyne prove to be crucial for the selectivity; especially a regiospecific annulation was achieved with sterically blocked substituents; namely, 2,4,6-trimetyl benzene or 2,4-dimethyl benzene. This approach enables the geometrically controlled synthesis of linear bispentalenes from 1,2,4,5-tetraethynylbenzene or 2,3,6,7-tetraethynylnaphthalene. Moreover, the annulation of a series of tetraynes with a different substitution pattern regioselectively provided the bispentalene scaffolds. A computational study revealed that this is the result of a kinetic control induced by the bulky NHC ligands.